AUDIT KAS DAN SETARA KAS: EVALUASI PROSEDUR AUDIT DAN REKOMENDASI PERBAIKAN SISTEM KAS UNTUK PERUSAHAAN BALAI LELANG - Fisdiana, Anggit Jelita; Wilasittha, Acynthia Ayu (Universitas Logistik dan Bisnis Internasional, 2025)
The main focus of this research is to evaluate the audit methods and procedures implemented, as well as to formulate Standard Operating Procedure (SOP) recommendations to strengthen the internal control system within the company. The audit procedures conducted by KAP STU include bank reconciliation and the evaluation of internal controls. This study employs a qualitative research method with a case study approach at PT A, an auction house company, by collecting data through interviews, field observations, and documentation. Based on the research findings, the audit procedures applied by KAP STU have followed the stages outlined in audit standards; however, weaknesses were identified in PT A’s internal control, which led to errors in the preparation of financial statements, particularly in the cash flow statement. The main recommendation provided is the implementation of SOPs consisting of regular cash counts, strict supervision, and systematic documentation archiving to strengthen the company’s internal control system. With the implementation of these SOPs, it is expected that PT A’s financial statements will become more accurate and reliable in the future.